Development of experimental firing test stand to study the rocket engine thrust characteristics - Wilton Fernandes Alves (2008)
The main aim of this work is to present the specification of an experimental firing test stand of liquid rocket engine (LRE), comprising the main design, the instrumentation of measurement system, the data acquisition system, the operating manual, as well as the methodology to perform laboratory work for determination of a LRE thrust characteristics in atmospheric conditions. Initially it is presented a theoretical basement of LRE in general and concerning the laboratory work. After that it is proposed a methodology for execution of laboratory work using resources of information technology, which will allow the automatic and remote functioning of the test stand, and it will give to the users the inputs necessaries to realization of tests and attainment of reliable results. The specification of the test stand is result of calculations implemented in MathCAD program in way of algorithms presented in appendix of this work. The control of mass flow rates of propellant by automatic pressure regulators and valves, as well as the data acquisition of test stand is carried out by Labview program in a NI PXI platform. The instrumentation of measurement system will make possible online measurements of temperatures, pressures, mass flow rates and thrust force related to the tests. It is presented also a preliminary analysis of type B uncertainties of test stand system, and a comparative analysis between designed LRE with similar rocket engine of a test stand in operation.